2018
DOI: 10.3390/cells7080093
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Vesicles in Cancer: Cargo, Function, and Therapeutic Implications

Abstract: Extracellular vesicles (EVs) are a heterogeneous collection of membrane-bound structures that play key roles in intercellular communication. EVs are potent regulators of tumorigenesis and function largely via the shuttling of cargo molecules (RNA, DNA, protein, etc.) among cancer cells and the cells of the tumor stroma. EV-based crosstalk can promote proliferation, shape the tumor microenvironment, enhance metastasis, and allow tumor cells to evade immune destruction. In many cases these functions have been li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 175 publications
(290 reference statements)
0
73
0
1
Order By: Relevance
“…Although, the reports have demonstrated possible mechanisms by which miRNAs and proteins (other than MMPs) are regulated for their secretion into EVs [ 44 , 45 , 46 ], nevertheless, the mechanisms regarding the secretion of MMPs into EVs remain largely unknown. Recently, it was shown that the stabilization of MMPs in MVBs and their secretion into EVs is regulated by cortactin [ 47 ].…”
Section: Mmps Secretion Into Evsmentioning
confidence: 99%
“…Although, the reports have demonstrated possible mechanisms by which miRNAs and proteins (other than MMPs) are regulated for their secretion into EVs [ 44 , 45 , 46 ], nevertheless, the mechanisms regarding the secretion of MMPs into EVs remain largely unknown. Recently, it was shown that the stabilization of MMPs in MVBs and their secretion into EVs is regulated by cortactin [ 47 ].…”
Section: Mmps Secretion Into Evsmentioning
confidence: 99%
“…Exosomes are released into extracellular space by fusion of multivesicular endosomes with the cell membrane, whereas microvesicles are developed directly from the cell membrane [172]. It has been demonstrated that EVs from neighboring cells can affect various biological properties of cancer cells, such as proliferation, metastasis, hypoxia tolerance, and therapeutic resistance [173,174]. For example, mitochondrial DNA in EVs derived from cancer-associated fibroblasts (CAFs) contributes to the development of resistance to hormone therapy in breast cancer [175].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Similarly, in liver cancer cells, CD90-positive cells were found to secrete EVs, that promote tube formation and cell-cell adhesion via the transfer of H19 lncRNA [129]. These results suggest, that subsets of tumor cells secrete EVs carrying a unique set of cargo capable of altering stromal cell phenotypes in specific ways [153].…”
Section: Molecular Cargo Of Tex Influencing Angiogenesis / Tex Convermentioning
confidence: 71%